Polysemic provocations of border negotiation - Charoula Stathopoulou; Peter Appelbaum (Universidade Estadual de Campinas, 2017)
Considering Ethnomathematics "as path to a renovated education" we discuss it together with curricular ideas exploring mathematics knowledge in different contexts and the communication/translation among them.  Permeable borders of mathematics education force translation that is rarely made visible to those involved: young learners move from school to home to various communities; teachers try to translate mathematical discourse into school cultures that can accommodate multiple student life languages of mathematics and learning. On the one hand we can say that curriculum is cultural translation (Moon, 2012). On the other hand, we can provoke translation as opportunity via the conception of Hannah Arendt that translation is a disruption that creates a moment of potential learning (Appelbaum, 2013). To support our perspective we use examples coming from ethomathematical research: ethnographic studies of the traditional practice of Xysta (Chios Island, Greece), and from young Roma learners of mathematics in Greece (Stathopooulou, 2005). Through these examples we explore possibilities for making the power relations, authorities, and cultural clashes of life and school mathematics explicit for the children who are asked to carry out translations. We do this as a provocation to action: Instead of a school mathematics curriculum that tries to make processes of translation easier for the learners, we seek a curriculum that recognizes the funds of knowledge that children bring to the understanding of cultural translation. Translation is both disruption that make learning possible as border pedagogy, and the place of carnival in an uncanny valley that resonates with possibility.